Phase relation between rotating phase locked (2, 1) and (3, 1) tearing modes in ASDEX Upgrade. (4th March 2021) - Gude, A; Maraschek, M; Igochine, V; Sieglin, B; Willensdorfer, M; Zohm, H
Abstract: Tearing modes are a major concern for large tokamak devices. Therefore their detection and characterization is of importance for timely countermeasures to avoid significant impact on the discharge or at least prevent possible machine damage. In case of phase-locked tearing modes, the poloidal variation of induced magnetic field fluctuation depends on the amplitudes of and the phase difference between the individual modes. This affects mode detection and identification when not considered appropriately. The phase between phase-locked (2, 1) and (3, 1) tearing modes in ASDEX Upgrade has been determined from local electron temperature and magnetic measurements independently. It is shown that the modes can be in phase at any poloidal position starting from the low field side plasma midplane over the plasma top to the high field side midplane. This observation invalidates the widespread assumption that phase-locked tearing modes are in phase near the low field side midplane. Dependence of the in-phase position on both, the plasma pressure and the plasma rotation velocity, is observed.